Status quo on fiscal decentralisation in Mongolia - Ariunnaa Lkhagvadorj (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2007)
This paper gives a review on the theoretical foundation for fiscal decentralisation and a status quo analysis of the intergovernmental relations in Mongolia. It consists of two parts. Part I briefly reviews the theories of fiscal decentralisation and its impact on the nations' welfare considering the major challenges for a transition economy. Part II of the paper describes the general structure and scope of the government and examines the current fiscal autonomy in Mongolia focusing on the four main areas of intergovernmental relations. This paper concludes that local governments in Mongolia are still far away from having the political, administrative and fiscal autonomy. New approaches for the assignments of expenditures and revenues in Mongolia are urgently needed.
urn:nbn:de:kobv:517-opus-16159
Keywords: H70; H71; H72; H76; H77; 330; Fiscal decentralisation; fiscal federalism; intergovernmental relations; local and regional autonomy; revenue sharing; economic transformation; Finanzföderalismus; Finanzausgleich; Mongolei